Implementation of Istiqomah Behavior in Tarawih Prayer as the Values of Sufism Among the Congregation of Al-Falaah Mosque - Gepira Enung Nurjanah; Kamalia Nurhikmah; Novy Maryani (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the implementation of istiqomah (consistency) behavior in Tarawih prayer as a Sufi value among the congregation of Masjid Al-Falaah, Bandung. Using a qualitative-phenomenological approach with in-depth interviews, participatory observation, and questionnaire distribution involving 10 regular congregants and 25 general respondents, this research reveals that Sufi values particularly maqamat (spiritual stages), ahwal (spiritual states), muraqabah (divine awareness), and ikhlas (sincerity) significantly support the consistency of Tarawih worship. Congregants who internalized these Sufi values demonstrated a 30% higher attendance rate. The 40–60% decline in participation after the second week of Ramadan can be systematically addressed through Sufi-based spiritual training programs, tazkiyatun nafs (soul purification), communal post-prayer spiritual activities, and structured knowledge building on Sufi concepts. The study also reveals that urbanization pressures, including shift work, long commutes, and pre-Eid preparation activities, disproportionately affect participation. Muraqabah training conducted prior to Ramadan improved retention by 15%. The communal dimension through study circles, collective dhikr, and post-Tarawih silaturahmi increased consistency by 30% among participating congregants. These findings contribute to Islamic character education discourse, particularly regarding the formation of istiqomah attitudes through a Sufi approach in urban Muslim communities.